(untitled) (Italian Journal of Public Health, 2010)
Health and wellbeing is the most value that a person can have [1]. Baccus, Tobacco and Venus want to give a chance to take an active awareness and knowledge, about people’s “health”, “safety” and “life” in order to tobacco, alcohol and sexually transmitted diseases themes, aiming to promote “prolonging life” through more scientific-oriented studies. In this context, it’s necessary base focus on social-economic and cultural challenges - occurred during 20th- century in most industrialized countries- and on progress - made over the last twenty years - occurred in countries whose rapidly growing economies and that have determined and conducted to wellbeing and to the hope of a better life, even if in some case within country differences could exist [2]. However, wellbeing, but also behavioural lifestyle-related diseases (especially chronic diseases), paradoxically grew at the same time. We must not forget that not only personal characteristics and behaviour, but also economic and cultural surroundings, are the determinants of health [3].